READINGS ON INSTALLATION OF READY-MADE - Renkci Tastan, Tugba (ISTANBUL KULTUR UNIV, 2016)
The installation, meaning placing in Turkish, has become often preferred an expression form of art in today's national and international art scene. In art history and today's art, there are various bases, many examples have been created and supported by different methods and techniques of installations. In this study, Installation, a very important form of expression in contemporary art, its definition, characteristics, appearance in today's literally and the artists are mentioned briefly. In the development section of the text, artists Joseph Kosuth and Nam June Paik, who demonstrate extraordinary works of art that generate discussion on this issue, have been dealt with an overview. In accordance with data; the purpose, the content and artistic movement of two installation projects have been presented by the author and been discussed on social issues. Finally in Conclusion part, comments and evaluations have been made on issues such as unity and spatial perception Art & Life. The purpose of the text; to mention the main points regarding the installation expression form, to provide a critical overview on the current topics with demonstration project and a visual narrative. Besides, a literary essay has been demonstrated with literature methods.
Keywords: Ready-Made; Installation; Visual Arts; Plastic Arts; Art